Pemberdayaan Masyarakat melalui Program Zakat Corporate Social Responbility PT Petrogas Jatim Utama Cendana Bersama Lembaga Manajemen Infaq di Dusun Caren - Dini Riyanti; Fauzatul Laily Nisa; Renny Oktafia (Pendidikan Matematika, FKIP Universitas Mataram, 2026)
Limited access to clean water remains a major challenge for rural communities, particularly in Caren Hamlet, Blitar Regency, where seasonal droughts significantly affect public health, productivity, and quality of life. Caren Hamlet is part of Wonotirto Village. Located near forest areas, hills, and agricultural land, around 70% of the population in Caren Hamlet is classified as economically disadvantaged and highly dependent on clean water availability for daily needs. This community empowerment program aims to improve access to clean water through a zakat-based Corporate Social Responsibility (CSR) initiative by PT Petrogas Jatim Utama Cendana, managed by Lembaga Manajemen Infaq (LMI). The program implementation involved several stages, including community needs assessment, participatory planning, bore well construction, and sustainability evaluation. The results show that collaboration among the company, zakat management institution, and local community was a key factor in the program’s success. Despite technical challenges related to geological conditions and non-technical challenges arising from social dynamics. Overall, the program not only addresses the basic need for clean water but also contributes to community welfare improvement and supports the achievement of Sustainable Development Goal (SDG) 6 on clean water and sanitation.